MIND-BODY INTEGRATIVE TREATMENT OF PSYCHODERMATOSES - Roberto Doglia Azambuja (European Medical Journal, 2017)
The mind-skin interaction has been progressively clarified by recent research that has focussed on psychoneuroimmunology. This article focusses on brain-cell communication by means of chemical messengers and the changes in the skin they provoke under stress, providing an origin to dermatoses linked to the mind, called psychodermatoses. The author refers to three types of psychodermatoses: those caused by prior psychiatric disturbances, those that cause psychologic disturbances by their aspect, and those that are influenced by emotional states. This article highlights the four simple and natural mind-body anti-stress techniques of posture, diaphragmatic breathing, muscle relaxation, and meditation that every doctor can teach to patients, which will enable them to face stressful situations and therefore protect themselves against the negative psychological effects of stress. Several therapeutic behaviours in the doctor-patient relationship are recommended to build a patient's trust in their doctor and to encourage the patient to play an important part in their treatment process. It is emphasised that the treatment of psychodermatoses needs to be co-operative, integrating specialists in dermatology, psychiatry, and psychology. Dermatologists take care of the skin alterations, while psychiatrists are involved with the associated mental disturbances and are able to prescribe a large range of psychopharmaceuticals to treat anxiety, depression, post-traumatic stress disorder, and compulsive states. Psychotherapists try to correct erroneous behaviours and false feelings, employing cognitive-behavioural therapy, analytic and reprogramming techniques, and also hypnosis, in order to rid patients of psycho-emotional perturbations and facilitate successful outcomes in the skin.